Analyzing Customer Engagement Through Customer Experience In Health Care Industry - Özçelik, Ayşe Bengi (Institute of Social Sciences, 2019)
The unilateral relationship between brand and consumer in 1980s has become a unilateral and interactive one in which consumer is empowered. This transformation increased the competition in market and changed the approach of organizations about their clients, accordingly the importance of consumer-brand interaction is increased. In 2000s, a paradigm shift is actualized in marketing in which the service become the focus. With this shift, it is widely accepted that the critical identity of a brand is built by the service provided even if the brand is a manufacturing one. Technological developments supported this transformation by putting the information flow forward and help consumers being empowered. Hence, experience has become the new focus of marketing by converting the traditional exchange relationship. Organizations should provide a well-designed experience story in order to sustain their existence in the market.

1980'li yıllardaki tek yönlü marka-tüketici ilişkisi, günümüzde tüketicinin güç kazandığı iki yönlü ve etkileşimli bir ilişkiye dönüşmüştür. Bu durum, pazardaki rekabeti arttırarak kurumların müşterilerine olan yaklaşımlarını değiştirmiş ve tüketici-marka etkileşiminin önemi artmıştır. 2000'li yıllar pazarlamada bir paradigma dönüşümüne sahne olmuş ve hizmetin ön plana çıktığı bir döneme girilmiştir. Markanın fark yaratan, kimliğini kazanmasını sağlayan özellik, o marka ne üretirse üretsin, hizmet olmaya başlamıştır. Teknolojik gelişmeler, tüketicinin yaşadığı süreci ve bilgi akışını ön plana çıkararak, deneyimi pazarlamanın klasik değişim (exchange) ilişkisini farklı bir boyuta taşıyan yeni bir odak olarak ortaya koymuştur. Kurumların, kendi varlıklarını kanıtlamak için tüketicilerine doğru bir deneyim hikayesi sunmaları gerekmektedir. Bu hikayeyi tüketiciden gelen bilgiyle ve tüketicinin nasıl bir yolculuk yaşadığını doğru analiz ederek tasarlamalıdırlar. Fakat bu analiz, tüketicilerin dijital ortamda sürekli olarak birbirleriyle etkileşim halinde olmaları ve birçok bilgiye sahip olarak güçlenmeleri sebebiyle git gide zorlaşmaktadı
Sağlık Sektöründe Müşteri Deneyimi Ve Müşteri Katılımı Analizi
Thesis (Ph.D) -- İstanbul Technical University, Institute of Social Sciences, 2019
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Experiential marketing; Health services; Quality of health care; Consumer services; Business to consumer; Deneyimsel pazarlama; Sağlık hizmetleri; Sağlık hizmetleri kalitesi; Servis pazarlaması